2021
DOI: 10.3390/v13101972
|View full text |Cite
|
Sign up to set email alerts
|

Function Is More Reliable than Quantity to Follow Up the Humoral Response to the Receptor-Binding Domain of SARS-CoV-2-Spike Protein after Natural Infection or COVID-19 Vaccination

Abstract: Both the SARS-CoV-2 pandemic and emergence of variants of concern have highlighted the need for functional antibody assays to monitor the humoral response over time. Antibodies directed against the spike (S) protein of SARS-CoV-2 are an important component of the neutralizing antibody response. In this work, we report that in a subset of patients—despite a decline in total S-specific antibodies—neutralizing antibody titers remain at a similar level for an average of 98 days in longitudinal sampling of a cohort… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 58 publications
2
20
0
Order By: Relevance
“…Further, it was clear that the functionality of adaptive immunological components is more important than just sole quantity [5]. In line with this, it became evident that a diagnostic focus should be on the neutralizing the potency of detected anti-SARS-CoV-2-antibodies [6,7].…”
Section: Introductionmentioning
confidence: 93%
“…Further, it was clear that the functionality of adaptive immunological components is more important than just sole quantity [5]. In line with this, it became evident that a diagnostic focus should be on the neutralizing the potency of detected anti-SARS-CoV-2-antibodies [6,7].…”
Section: Introductionmentioning
confidence: 93%
“…Recently, more studies are exploring the efficacy of the natural immune response to SARS-CoV-2 vs. the mRNA vaccine-elicited response [22][23][24][25]. Our most recent work confirmed that following a natural infection, neutralizing antibody (nAbs) titers generated during infection accompanied by vaccination are significantly better in function than those generated by vaccination alone [26]. To this end, in this study, we compared the neutralization capacity of previously infected individuals and healthy previously unexposed individuals before and after vaccination against several variants of concern (VOCs) using a surrogate viral neutralization assay [27].…”
Section: Introductionmentioning
confidence: 56%
“…There is growing, but still limited, information available on immunity against the viral variants conferred by natural infection with the authentic SARS-CoV-2 strain or by the mRNA COVID-19 vaccines. Using samples collected during the COVID-19 pandemic, most of them before the documented introduction of the variants in the jurisdiction of Puerto Rico [26,28], we attempted to compare the kinetics of the nAbs response in the context of individuals with naturally acquired infection (pre-exposed) and unexposed individuals, following vaccination, via a widely used sVNT detecting RBD-targeting antibodies [26,[29][30][31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collectively, Seronet institutions reported development of 27 in-house ELISA methods (Table 1). 6,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] The majority of ELISA methods were developed for testing of serum and/or plasma, with additional methods available for testing dried blood spots (DBS), saliva/oral fluid, and breast milk. Two methods have been granted FDA EUA approval, 3 methods are pending FDA EUA, 4 methods are validated for high-complexity testing in a CLIA-certified laboratory, and 18 methods are for research-use only (RUO).…”
Section: Seronet Serology Assay Datamentioning
confidence: 99%